2015
DOI: 10.1186/s13567-014-0125-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bovine leukemia virus infection on milk neutrophil function and the milk lymphocyte profile

Abstract: The effects of bovine leukemia virus (BLV) on the immune response have been extensively investigated; however, its effects on mammary gland immunity are only speculative. Although BLV has a tropism for B cells, it can affect both adaptive and innate immunities because these systems share many effector mechanisms. This scenario is the basis of this investigation of the effects of BLV on mammary gland immunity, which is largely dependent upon neutrophilic functions. Thus, the present study sought to examine neut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
35
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 59 publications
3
35
0
3
Order By: Relevance
“…The most distinguishing feature of BLV infection, even at low leukocytosis, is the disappearance of the normally correlated links between the counts of different populations of leukocytes, indicating the destruction of the network relationships between them. Importantly, in animals with high leukocytosis, marked neutrophilopenia is observed, which coincides with the literature data on the change in the neutrophil content in milk at BLV infection and high leukocytosis [11]. Given the need for a simpler method for identifying the most infectious animals in industrial herds, it seems appropriate to simultaneously evaluate the viral load (the amount of BLV RNA in the peripheral blood) and the severity of leukocytosis.…”
Section: Erythrocyte and Leukocyte Profiles Of Peripheral Blood In Blsupporting
confidence: 85%
See 2 more Smart Citations
“…The most distinguishing feature of BLV infection, even at low leukocytosis, is the disappearance of the normally correlated links between the counts of different populations of leukocytes, indicating the destruction of the network relationships between them. Importantly, in animals with high leukocytosis, marked neutrophilopenia is observed, which coincides with the literature data on the change in the neutrophil content in milk at BLV infection and high leukocytosis [11]. Given the need for a simpler method for identifying the most infectious animals in industrial herds, it seems appropriate to simultaneously evaluate the viral load (the amount of BLV RNA in the peripheral blood) and the severity of leukocytosis.…”
Section: Erythrocyte and Leukocyte Profiles Of Peripheral Blood In Blsupporting
confidence: 85%
“…When the pathogen is phagocytized, neutrophils produce free radicals that destroy it. It was found that in milk of cows infected with BLV, neutrophils are significantly reduced [11], while for individuals with leukocytosis and high load of BLV proviral DNA a reduced expression of -interferon (IFN-) by peripheral blood monocytes is characteristic. IFN-γ promotes phagocytosis and production of free radicals by neutrophils, which can, in particular, explain the decrease in neutrophil function along with the decrease in their number in BLV infected cows.…”
Section: Erythrocyte and Leukocyte Profiles Of Peripheral Blood In Blmentioning
confidence: 99%
See 1 more Smart Citation
“…The phagocytosis of PI labeled E. coli was assessed via flow cytometry (Della Libera et al, 2015). In brief, neutrophils (2×10 5 neutrophils) were seeded into duplicate wells of a 96-well, flat bottom cell culture plate.…”
Section: Phagocytosismentioning
confidence: 99%
“…BLV infection negatively impacts on dairy production by diminishing the milk yield and increasing deaths and veterinary costs. Moreover, it has been described that BLV infection might lead to a higher susceptibility to other infections due to its effects on immune cells (Della Libera et al, 2015;Emanuelson et al, 1992;Erskine et al, 2011;Frie and Coussens, 2015). In this way, BLV could be related to an increased incidence of mastitis, one of the most common diseases in dairy cattle.…”
mentioning
confidence: 99%